Foreign bodies in the digestive tract. Flexible endoscopy treatment: Foreign bodies in the digestive tract. Flexible endoscopy treatment - Piazze, Alvaro (Cirugía del Uruguay, 2005)
In the USA there occur approximately 1500 yearly deaths due to ingestion of extraneous bodies (EBs). T hose in charge of endoscopic urgencies are frequently cal/ed upan due to the patien's notion of having ingested an extraneous body. Clínica/ presentation varíe. Even though the majority of extraneous bodies pass through spontaneously (80- 90%), 10 to 20% require endoscopy and 1% has need of surgery Fibroendoscopy helps to so/ve the majority of cases and has displaced rigid endoscopy